2013
DOI: 10.1186/1471-2474-14-109
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish version of OMAS is a reliable and valid outcome measure for patients with ankle fractures

Gertrud M Nilsson,
Magnus Eneroth,
Charlotte S Ekdahl

Abstract: BackgroundThe aim of this study was to evaluate the test-retest reliability and the validity of the self-reported questionnaire Olerud-Molander Ankle Score (OMAS) in subjects after an ankle fracture.MethodsWhen evaluating the test-retest reliability of the OMAS, 42 subjects surgically treated due to an ankle fracture participated 12 months after injury. OMAS was completed by the patients on two occasions at one to two weeks’ interval. Concurrent criterion validity was evaluated using the five subscales of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 46 publications
5
54
4
1
Order By: Relevance
“…In this version, the test-retest reliability was calculated using both the Spearman rank correlation coefficient and ICC. 17 The authors reported excellent values of rho = 0.95 and ICC = 0.94, which are similar to our results. The first assessment of the OMAS-TR was completed at the clinic and the second assessment via phone interview with a total of 100 patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this version, the test-retest reliability was calculated using both the Spearman rank correlation coefficient and ICC. 17 The authors reported excellent values of rho = 0.95 and ICC = 0.94, which are similar to our results. The first assessment of the OMAS-TR was completed at the clinic and the second assessment via phone interview with a total of 100 patients.…”
Section: Discussionsupporting
confidence: 91%
“…These are not major or relevant complaints of patients with ankle fractures. On the other hand, Nilsson et al 17 reported that the correlation between the Swedish version OMAS and FAOS-ADL and FAOS-S subscales were 0.80 and 0.85, respectively, which is very similar to our validation results with the OMAS-TR and FAAM subscales. In addition, to determine convergent and divergent validity, we determined the level of associations between the scores on the OMAS-TR and the two summary scores for the SF-12.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nilsson et al suggested that a difference of 4.4 points in the Olerud Molander score is of clinical interest for a group of patients [ 52 ]. This meta-analysis shows an even greater difference in the Olerud Molander score of 6.88 points on short-term in favour of active mobilization and 8.00 points on long-term in favour of early weight-bearing.…”
Section: Discussionmentioning
confidence: 99%
“…112 More recently, additional evidence supporting the validity and reliability of the OMAS has been published. 113 In the context of the AIM trial, the conclusions drawn from the OMASs are supported by the high precision of estimates and the consistency with the secondary outcomes [SF-12 (mental and physical), EQ-5D and EQ-5D VAS, timed up and go test, ankle range of motion and pain].…”
Section: Internal Validity and Methodologymentioning
confidence: 97%